Thermionic Emission from Diamond Films in Molecular Hydrogen Environments - Paxton, William F.; Ravipati, Srikanth; Brooks, Morgan M.; Howell, Mick; Davidson, Jim L. (Frontiers in Mechanical Engineering, 2017)
Diamond-based low work function thermionic electron emitters are in high demand for applications ranging from electron guns and space thrusters to electrical energy converters. A key requirement of such diamond-based electron sources is hydrogen termination of the surfaces which can significantly reduce the emission barrier. However, at high temperatures (> 600°C), terminated hydrogen begins to desorb causing degradation in thermionic emission performance. The purpose of this study is to examine low-pressure hydrogen operating environments as a means to overcome this high temperature performance limitation by enabling increased thermionic emission currents with improved stability at temperatures > 600°C. A series of isothermal and isobaric experiments were performed in both nitrogen and hydrogen gas environments to determine the performance enhancement. Diamond electron emitters in both the as-grown and hydrogenated states were characterized at temperatures of 600°C, 625°C, and 650°C. An increase in thermionic emission current over vacuum operation was observed following the introduction of hydrogen. Upon evacuation of hydrogen to vacuum, the emission current decreased back to baseline levels. Further experiments in gas environments at a constant pressure (~5.5 x 10-6 Torr) were conducted at temperatures ranging from 700-900°C. It was observed that the hydrogen environment promoted increased emission current while also enabling the diamond electron emitters to stably emit at increased temperatures compared to vacuum operation. Analogous experiments using nitrogen environments did not show any measurable performance enhancements, thus verifying that hydrogen is responsible for the observed effect. These results suggest diamond-based electron emitters can have improved thermionic emission performance at temperatures > 600°C when operating in hydrogen gas environments.